Comparison of rainy season onset, cessation and duration for Ghana from RegCM4 and GMet Datasets - Mensah, Caleb; Amekudzi, Leonard K.; Klutse, Nana Ama B.; Aryee, Jeffrey N. A.; Asare, Kofi (Atmospheric and Climate Sciences, 2019)
An article published by Atmospheric and Climate Sciences and available at http://dx.doi.org/10.4236/acs.2016.62025